The Unique Fiber Anatomy of Middle Temporal Gyrus Default Mode Connectivity. Issue 1 (30th April 2021) - Briggs, Robert G; Tanglay, Onur; Dadario, Nicholas B; Young, Isabella M; Fonseka, R Dineth; Hormovas, Jorge; Dhanaraj, Vukshitha; Lin, Yueh-Hsin; Kim, Sihyong J; Bouvette, Adam; Chakraborty, Arpan R; Milligan, Ty M; et al.
Abstract: BACKGROUND: The middle temporal gyrus (MTG) is understood to play a role in language-related tasks such as lexical comprehension and semantic cognition. However, a more specific understanding of its key white matter connections could promote the preservation of these functions during neurosurgery. OBJECTIVE: To provide a detailed description of the underlying white matter tracts associated with the MTG to improve semantic preservation during neurosurgery. METHODS: Tractography was performed using diffusion imaging obtained from 10 healthy adults from the Human Connectome Project. All tracts were mapped between cerebral hemispheres with a subsequent laterality index calculated based on resultant tract volumes. Ten postmortem dissections were performed for ex vivo validation of the tractography based on qualitative visual agreement. RESULTS: We identified 2 major white matter bundles leaving the MTG: the inferior longitudinal fasciculus and superior longitudinal fasciculus. In addition to long association fibers, a unique linear sequence of U-shaped fibers was identified, possibly representing a form of visual semantic transfer down the temporal lobe. CONCLUSION: We elucidate the underlying fiber-bundle anatomy of the MTG, an area highly involved in the brain's language network. Improved understanding of the unique, underlying white matter connections in and around this area may augment our overall understanding of language processing as well as the involvement of higher order cerebral networks like the default mode network in these functions.